Liquefied Petroleum Gas Transport Service Improvement via Telematics Support - Szpytko, Janusz; Hurtado, Lenier Aleman; Duarte, Yorlandys Salgado (Development of Transport by Telematics, 2019)
In developing countries, there are cases where the transport fleets are not subjected to scheduled services/maintenance or there are no maintenance procedures. The observed situation is the result of a shortage of required exploitation resources. The subject of the paper are solutions aimed at improving the service of the liquefied petroleum gas (LPG) transport with the use of telematics applications (information and communications technology, ICT). As result of the analysis of various strategies, a predictive maintenance type model was selected. The method of designing a predictive maintenance model of transport devices was presented, in which tele-information techniques (telematics) were proposed (to obtain information on the technical condition device). The operational parameters were identified, which will be the subject of registration, and then analysis and synthesis for decision-making purposes.